Eosinophilic Angiocentric Fibrosis of the Nasal Septum. (24th March 2013) - Li, Yunchuan; Liu, Honggang; Han, Demin; Zang, Hongrui; Wang, Tong; Hu, Bin
Abstract : Background . Eosinophilic angiocentric fibrosis (EAF) is a rare benign condition of unknown aetiology that causes stenosis of the upper respiratory tract. It is most commonly found at the nasal septum and sinus mucosa causing mucosal thickening and nasal obstructive symptoms. The diagnosis is mainly based on characteristic histologic findings. Case Report . A 27-year-old young woman presented with a slow growing mass at her anterior nasal septum for over eight years. She complained of persistent nasal obstruction, epistaxis, sometimes diffused facial pain, and chronic headache. 3 years ago, the tumor was partially resected for ventilation and a nasal septum perforation was left. Imaging findings indicated soft-tissue thickening of the anterior part of septum and adjacent lateral nasal walls. Pathological examination showed numerous inflammatory cells infiltrates containing eosinophils, fibroinflammatory lesion with a whorled appearance fibrosis which typically surrounded vessels. A diagnosis of eosinophilic angiocentric fibrosis was made. All laboratory tests were unremarkable. Skin prick test was positive. The tumor-like lesion was totally resected. Conclusions . EAF is a rare benign and progressive disorder causing destruction. Combined with radiological imaging of EAF historical findings contribute to the diagnosis. It is important to prevent tumor from recurrence by total resection of the lesion.